Development of design advisor tools of upstream processing for biopharmaceutical production - Othman, Nurmala Idayu (2017)
Unstructured and structured kinetic model is used in introducing the production of monoclonal antibody starting from cell growth, substrates uptake until the antibody is produce. Basically, the production of monoclonal antibody are varies depending on the cell used. Thus, take time in the conformation of the production rate by the experimental data. A design advisor tool that focuses on upstream processing of biopharmaceutical production is developed in this research. The upstream process of monoclonal antibody production will be used as a reference model and it is limited to batch processing only. The unstructured model of kinetic equation is used in the growth model of the cell culture. MATLAB program is used to produce the command setting as well as the graphical user interface which is used to develop the advisor tool. The design advisor tool is tested and verified through a base case study of conceptual design of monoclonal antibody production which is performed by Kyparissidis in 2010 based on the kinetic parameter that is introduced by Kontoravdi in 2010. The developed advisor tool was able to predict the progress of cell growth, products formation, and the substrates uptake of the cells which is glucose and glutamate, and also the production of monoclonal antibody.